Penerapan Model Problem Based Learning dalam Meningkatkan Kemampuan Pemahaman Konsep Matematika Materi Pecahan di SD - Oktari, Nunung; Faudiah, Nyiayu Fahriza; Ningsih, Yunika Lestaria (PPSDP Undergraduate Journal of Educational Sciences, 2025)
Understanding mathematical concepts can be interpreted as the most important part of learning mathematics. Increasing understanding of mathematical concepts needs to be pursued for the sake of students' success in learning. Understanding concepts is one of the mathematical skills or proficiency that is expected to be achieved in learning mathematics, especially in fraction material in elementary school. The problem of this research is the low ability to understand mathematical concepts in fraction material in elementary school. This research aims to determine improvements in fraction material through the problem-based learning model. The method used in Pre-Experimental research is One-Group pretest posttest type. The subjects used by this researcher were class III of SD Negeri 1 Teluk Kijing, totaling 16 students. The data analysis techniques used by researchers are descriptive statistical analysis techniques, completeness analysis techniques for learning outcomes, student response questionnaire data analysis techniques, student learning activity observation data analysis techniques and normalized gain analysis techniques (N-Gain).